Potential Of Keprok Citrus (Citrus nobilis) From Lembang West Java For Dental Email Cleaning - Euis Reni Yuslianti; Hartanto Endrowahyudi; Asih Rahaju; Orin Oktarina (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Consumption of colored foods and drinks can cause tooth discoloration, synthetic whitening agents are used to increase the degree of brightness of tooth color but have many side effects. Tangerine (Citrus nobilis) is a natural ingredient that is used by the community for whitening the color of teeth safely and with minimal side effects. This study aims to determine the potential of the ethanol extract of tangerine peels to whiten teeth in terms of the degree of color brightness and tooth enamel surface roughness. Material and Methods: This research analytic laboratory experiments. Samples used 30 premolars that had been soaked in coffee, divided according to the concentration of tangerine peel extract 25%, 50%, and 75% then each group was exposed to 1x30 and 2x30 minutes. Tooth discoloration seen from the value of the degree of color brightness and tooth enamel surface roughness before and after exposure was analyzed using the paired T test and Univariate GLM test (P<0.05).  Results and Discussions: The result showed there were differences in the effect of ethanol extract of tangerine peel on the brightness of the color and roughness of tooth enamel at various concentrations before and after treatment and there was an interaction effect between concentrations of 25%, 50%, and 75% and exposure time of 1x30 and 2x30 minutes which was significant with p=0 .00. Conclusion: It can be concluded that ethanol extract of tangerine peel has the potential to whiten teeth as seen from the degree of color brightness and tooth enamel surface roughness.